A new nation - Otis, Daniel Henry (My University, 1892)
Introduction: We of today look back with pride to the time our forefathers established a republic that should be the boast of the nineteenth century. We point with a spirit of reverence to those heroes who in the time of a nation’s peril voluntarily laid down their lives to solve the vexed question of human slavery. We all agree that by these means we have reached a degree of development never before attained. And yet while thus congratulating ourselves, we hear from all sides of the wonderful opportunity for improvement. Such questions as the tariff, the labor problem, and the free coinage of silver are presenting themselves each with their special claims. But in our eagerness to discuss these issues, we are very apt to neglect one very important question. A question that if properly solved would put an end to the existence of these others. This question arises from our system of competition. Go into any of our large cities and there you will see that the struggle for existence is a perpetual warfare. A merchant spends his time and energy not in advancing the interests of the community but in getting his neighbor out of the way.
Citation: Otis, Daniel Henry. A new nation. Senior thesis, Kansas State Agricultural College, 1892.
Morse Department of Special Collections
Keywords: Nation; Slavery; Amendments; Government; Political science; Theses; Manuscripts (documents)